2015
DOI: 10.3856/vol43-issue1-fulltext-24
|View full text |Cite
|
Sign up to set email alerts
|

Strongly directional and differential swimming behavior of an adult female white shark, Carcharodon carcharias (Chondrichthyes: Lamnidae) from Guadalupe Island, Mexico

Abstract: ABSTRACT.We report on an adult female white shark tracked for 288 days and 7,100 km in the NE Pacific Ocean. The shark, tagged with a real-time satellite tag off Guadalupe Island, Mexico in October 2006, remained around the island for 3.5 months but left in early February 2007 for a ca. 3,900 km westward migration. Heading and swimming speed data showed that: a) the arc-like route followed by this shark during oceanic travel involved strongly directional rapid movement, and b) once the shark arrived to a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Knowledge about C. carcharias around Guadalupe Island is derived from a limited number of studies related to migration (Domeier & Nasby‐Lucas, ), ecology (Becerril‐García, ; Bonfil & O'Brien, ; Hoyos‐Padilla, Klimley, Galván‐Magaña, & Antoniou, ; Jaime‐Rivera, Caraveo‐Patiño, Hoyos‐Padilla, & Galván‐Magaña, ), and local movements (Hoyos‐Padilla et al, ; Skomal, Hoyos‐Padilla, Kukulya, & Stokey, ). There is no ethological research describing the surface behaviour of white sharks related to cage‐diving boats in Mexico or in the whole eastern Pacific, despite its importance for the Mexican authorities (Becerril‐García, ; Torres‐Aguilar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about C. carcharias around Guadalupe Island is derived from a limited number of studies related to migration (Domeier & Nasby‐Lucas, ), ecology (Becerril‐García, ; Bonfil & O'Brien, ; Hoyos‐Padilla, Klimley, Galván‐Magaña, & Antoniou, ; Jaime‐Rivera, Caraveo‐Patiño, Hoyos‐Padilla, & Galván‐Magaña, ), and local movements (Hoyos‐Padilla et al, ; Skomal, Hoyos‐Padilla, Kukulya, & Stokey, ). There is no ethological research describing the surface behaviour of white sharks related to cage‐diving boats in Mexico or in the whole eastern Pacific, despite its importance for the Mexican authorities (Becerril‐García, ; Torres‐Aguilar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…During periods of directed horizontal travel a white shark (2.9 m TL large, juvenile female, NS2018-06) was shown to shift to a pattern of increased near-surface swimming punctuated by occasional deep dives. A number of white shark tracking studies have reported a similar pattern of increased surface swimming (Bonfil et al, 2005;Weng et al, 2007a;Domeier and Nasby-Lucas, 2008) and increased swimming speed (Bonfil and O'Brien, 2015;Watanabe et al, 2019) during traveling or oceanic phases. However, white sharks moving directly at the surface incur wave drag, which is energetically costly (Watanabe et al, 2019).…”
Section: Seasonality and Migrationmentioning
confidence: 88%
“…During periods of directed horizontal travel a white shark (2.9 m TL large, juvenile female, NS2018-06) was shown to shift to a pattern of increased near-surface swimming punctuated by occasional deep dives. A number of white shark tracking studies have reported a similar pattern of increased surface swimming (Bonfil et al, 2005;Weng et al, 2007a;Domeier and Nasby-Lucas, 2008) and increased swimming speed (Bonfil and O'Brien, 2015;Watanabe et al, 2019) during traveling or oceanic phases. However, white sharks moving directly at the surface incur wave drag, which is energetically costly (Watanabe et al, 2019).…”
Section: Seasonality and Migrationmentioning
confidence: 88%